2020
DOI: 10.3201/eid2611.191766
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Timeliness of Outbreak Response in the World Health Organization African Region, 2017–2019

Abstract: Large-scale protracted outbreaks can be prevented through early detection, notification, and rapid control. We assessed trends in timeliness of detecting and responding to outbreaks in the African Region reported to the World Health Organization during 2017–2019. We computed the median time to each outbreak milestone and assessed the rates of change over time using univariable and multivariable Cox proportional hazard regression analyses. We selected 296 outbreaks from 348 public reported health events and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…WHO AFRO’s Weekly Bulletin on Outbreaks and Emergencies provides an existing template which can feed into such a global database [ 20 ]. WHO AFRO has used this tool to provide annual metrics of timeliness in outbreak response for epidemic-prone diseases from 2017 to 2019, demonstrating reduced time from symptom onset of the primary case to outbreak detection (defined as alerting national authorities) from 14 (IQR 6–37) days in 2017 to 4 (IQR 1–11) days in 2019 [ 188 ].…”
Section: Discussionmentioning
confidence: 99%
“…WHO AFRO’s Weekly Bulletin on Outbreaks and Emergencies provides an existing template which can feed into such a global database [ 20 ]. WHO AFRO has used this tool to provide annual metrics of timeliness in outbreak response for epidemic-prone diseases from 2017 to 2019, demonstrating reduced time from symptom onset of the primary case to outbreak detection (defined as alerting national authorities) from 14 (IQR 6–37) days in 2017 to 4 (IQR 1–11) days in 2019 [ 188 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the epidemic intelligence activities undertaken at AFRO may have contributed to the early detection of outbreaks and indirectly influenced the timeliness of WHO response actions to support member states in mounting public health response to outbreaks with potential for international spread. Impouma et al found that the timeliness of detection and control of outbreaks across the African region improved from 2017 to 2019, attributed to enhanced epidemic intelligence, among other factors [45]. For example, in 2017 WHO received initial information on a cluster of cases presenting with EVD-like symptoms in the Democratic Republic of the Congo three days before the event was confirmed and officially notified by the country.…”
Section: Discussionmentioning
confidence: 99%
“…These represented 2.3% of the confirmed COVID-19 cases and 2.3% of COVID-19-related deaths globally [ 2 ]. This figure, although small, is significant in a region that records more than 100 significant public health emergencies annually [ 3 ], many of which result in high morbidity, mortality, disability and socioeconomic disruptions, threatening national, regional and global health security. As a result, the region developed robust infectious disease control regimens well before the current COVID-19 pandemic [ 4 – 6 ].…”
mentioning
confidence: 99%
“…These initiatives have tangible, measurable outcomes in terms of number of events detected, speed of detection of events and speed of response to events [ 3 ]. Time to detection of events decreased from 14 days in 2017, to 7 in 2018 and 4 in 2019, while outbreaks ended faster; the time to declaration of end of outbreak decreased from 131 days in 2017 to 45 days in 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation